Legal Voids in the Regulation of Immaterial Compensation and the Role of General Court Judges in Building Progressive Judicial Standards - Ismu Bahaiduri Febri Kurnia; Azis Budianto (Konsensus : Jurnal Ilmu Pertahanan, Hukum dan Ilmu Komunikasi, 2026)
This study aims to analyze the legal vacuum and normative ambiguity in the regulation of immaterial damages in Indonesian civil law and reconstruct the role of general court judges in developing progressive judicial standards. Normatively, Articles 1243, 1246, and 1365 of the Civil Code recognize the existence of "loss" as a basis for awarding compensation, but do not provide an explicit definition, objective parameters, or quantification standards for immaterial losses. This condition creates a wide scope for judges' discretion and impacts disparity in decisions in general judicial practice, thereby weakening legal certainty and predictability. The study employs a normative juridical method with a statutory and conceptual approach to examine the construction of norms, court decision practices, and the legitimacy of legal discovery by judges based on the Law on Judicial Power. The study results indicate that the vacuum in the regulation of immaterial damages quantification requires an active role of judges in conducting legal discovery in a measured manner through the application of the principles of proportionality, propriety, and substantive justice. As a model for legal reform, this study recommends jurisprudence consolidation and judicial guidelines development by the Supreme Court to establish consistent and accountable standards. Thus, general court judges function not merely as mouthpieces of the law, but as actors in legal reform within a state based on the rule of law that ensures a balance between certainty and justice.